Upaya Penanggulangan Kenakalan Remaja : Studi Kasus Lingkup Desa Fadorolauru Kecamatan Hiliduho - Winda Junte Mendrofa; Daria Darmawati Gea; Hendrikus Otniel Nasozaro Harefa (Lembaga Pengembangan Kinerja Dosen, 2025)
In this case, juvenile delinquency is a social problem and of course has a negative impact, especially on the development of today's young generation. This study refers to juvenile delinquency that occurs especially in rural areas, the case study is precisely in Fadorolau village. This study aims to determine the forms of juvenile delinquency that occur in Fadorolau village and to find out and explore information on what efforts or attempts are made by the community, especially in government, state security and education in overcoming juvenile delinquency and alleviating the impact of juvenile delinquency, especially for young people. For this reason, the method used in the study is a qualitative approach by collecting data through observation, in-depth interviews and documentation to several individuals starting from government, state security and education and also exploring information from teenagers around the village. The conclusion in overcoming juvenile delinquency requires an integrated approach and of course will continue to be sustainable by involving all elements of society.